Monitoring metabolic side effects of atypical antipsychotics in people with an intellectual disability. (September 2013) - Teeluckdharry, Sadira; Sharma, Sujit; O'Rourke, Elizabeth; Tharian, Priyanka; Gondalekar, Anjali; Nainar, Feroz; Roy, Meera
This audit was undertaken prospectively to examine the compliance of a group of psychiatrists against guidelines they developed for monitoring the onset of metabolic syndrome, a potential side effect of antipsychotic medication, especially second generation or atypical ones. Phase 1 of the audit was to set standards by a questionnaire survey of participating psychiatrists against Consensus Guidelines on monitoring (American Diabetic Association, 2004), which they favoured. The results led to modifying these guidelines to develop minimum acceptable standards against which their practice was audited in Phase 2. Although in Phase 1, 77% of the psychiatrists felt that they did some baseline recording, Phase 2 finding did not corroborate this – only 53.8% of the notes recorded the assessment of risk factors in personal history; 37.5% risk factors in family history; 31.7% baseline weight and 26.4% baseline blood sugar/lipid levels. In Phase 1, 85% of the psychiatrists thought that they carried out some of the recommended monitoring; our audit found the records of weight monitoring in 69.7% of the notes and blood sugar and lipids monitoring in 44.2%. People with intellectual disability have a shorter life expectancy and increased risk of early death when compared with the general population. Obesity is already a health issue for people with intellectual disability. We discuss the challenges faced by psychiatrists in implementing their own minimum acceptable standards and suggest measures to reduce the metabolic risk associated with antipsychotic medication through increasing awareness – use of information leaflets in accessible format, health promotion and use of side effect checklists and improving access – by working collaboratively with general practitioners utilising the forum of annual health checks.